EUROPEAN UNION REFORM AND THE NEED FOR THE REFORMS OF THE NATIONAL SOCIO-ECONOMIC SYSTEMS - Carmen RADU; Liviu RADU (Challenges of the Knowledge Society)
This article seeks to analyze the time-being by means of the possibilities to reform public policies (at national and European level) which concern the economic and social area. The national and European social and economic well-being depends on the sustainability of the economic and social policies and on the determination to reform the system. We are considering the analysis of the evolution of the governmental policies regarding the status and evolution of labor force, the pension system and the assumption of the key structural reforms for economy and public administration. The economic resources required for the reform are affected by the new challenges emerged internationally: a potential new economic crisis, the management of the developments emerged on the energy markets, the management of the withdrawal of the United Kingdom from the European Union, etc.